Designing and delivering inclusive heritage tours: Good practices for engaging socially excluded audiences - Minnaert, Lynn (Turyzm/Tourism, 2025)
People who experience social exclusion often face barriers to participation in recreation and tourism and tend to have limited engagement with culture and heritage. Yet, both sets of activities have been linked to a range of positive outcomes. This study focuses on heritage tours, a tourism product at the crossroads of culture, tourism and recreation. It examines how heritage tours can be designed and delivered in a way that promotes inclusion: removing barriers, creating a judgement-free environment, fostering inclusive oral communication, and providing an equitable experience for all participants. Addressing a gap in the tourism literature, the paper draws on audience development strategies that have been used in culture and the arts, including product-led and marketled approaches. It analyzes a case study initiative in Edinburgh, Scotland, to explore the effectiveness of its approach and evaluate whether it offers any good practices that can be replicated in other destinations or contexts.